2017
DOI: 10.4103/jfmpc.jfmpc_186_17
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound in diagnosis and evaluation of bladder tumors

Abstract: Introduction:Bladder tumors are common and the only way to prove it is cystoscopy which is invasive and expensive. Finding noninvasive, well-accepted, and cost-effective method for early detection of bladder cancer is necessary. The aim of this study was to evaluate the role of ultrasonography in the diagnosis and evaluation of bladder tumors.Methods:This study was conducted on 75 patients with indications for cystoscopy. After recording demographic data, ultrasound, and cystoscopy was performed for all patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…The authors of this article suggest that while in patients with confirmed low-risk (pTa LG) bladder cancer the follow-up cystoscopy, other than the first one after bladder tumor resection, may be safely postponed for a period of a few months, as even active-surveillance has been reported to be safe in those patients [ 9 , 10 ] and thus delaying a recurrence diagnosis may not actually pose danger, in patients with high risk or unknown risk (primary) disease performing a cystoscopy, if possible to maintain adequate safety standards, is a must. In patients with a suspicion of a primary bladder tumor, an abdominal ultrasound may be considered in place of a cystoscopy, as its sensitivity has been reported to be very high [ 11 ]. Thirdly, as the availability of particular management modalities may be currently limited, the urologist must ascertain that the recommended diagnostic and treatment plan is feasible, for example by postponing currently unavailable imaging testing and substituting it with more accessible work-up.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of this article suggest that while in patients with confirmed low-risk (pTa LG) bladder cancer the follow-up cystoscopy, other than the first one after bladder tumor resection, may be safely postponed for a period of a few months, as even active-surveillance has been reported to be safe in those patients [ 9 , 10 ] and thus delaying a recurrence diagnosis may not actually pose danger, in patients with high risk or unknown risk (primary) disease performing a cystoscopy, if possible to maintain adequate safety standards, is a must. In patients with a suspicion of a primary bladder tumor, an abdominal ultrasound may be considered in place of a cystoscopy, as its sensitivity has been reported to be very high [ 11 ]. Thirdly, as the availability of particular management modalities may be currently limited, the urologist must ascertain that the recommended diagnostic and treatment plan is feasible, for example by postponing currently unavailable imaging testing and substituting it with more accessible work-up.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, CEUS can serve as a noninvasive approach for postoperative follow-up or in high-risk NMIBC patients, suggesting the potential to avoid early repeated resection (Re-TURB) offering valuable imaging information and with consequential socioeconomic implications and impact on health-care-related costs. Second, we would like to emphasize the potential role of CEUS as a first-line approach in patients with hematuria, as conventional US techniques, such as greyscale US and color Doppler ultrasound (CDUS), exhibited limited effectiveness in diagnosing malignant disease [26]. Nonetheless, previous studies concluded that tumor vascularity and lesion size detected by CDUS did not align with tumor stage and histological grade [27].…”
Section: Discussionmentioning
confidence: 99%
“…This limitation gave rise to the necessity for alternative diagnostic tools. Ultrasound can be a valuable tool, however it is not always diagnostic, while the option of CT scanning presents a major disadvantage, that is, radiation exposure for pregnant individuals [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%